The Stability of Change: State and Public Policies during Leftist Administrations in Uruguay (2005- 2020) - Germán Bidegain; Martín Freigedo; Cristina Zurbriggen (Cuadernos de Economía)
This article examines the 15-year trajectory of Uruguay’s leftist administrations, focusing on the influence of the Frente Amplio (FA) on public policy and state configuration. It scrutinizes the challenges of and progress in state strengthening and policy shaping through three thematic blocks. The conclusion reflects on the enduring impacts of the transformative phase, marked by heightened state influence on public policy, economics, and social affairs. It showcases the feasibility of pursuing a redistributive agenda while upholding stability and resilience in the 21st-century Uruguayan state apparatus.